Female labour force participation in Malaysia / Lim Li Huan - Lim , Li Huan (2020)
The main objective of this study is to analyse the participation rate of the female labour force in Malaysia in 2015. The female labour force participation rate is the per cent of the female population ages 15 and above are economically active, either by working or by looking for work. Since the independence of Malaysia, the participation of women tends to be lower than men labour force in the labour market. However, these gender differences in labour participation rate have been narrowing substantially in recent decades. The increase in the female labour force may due to education opportunities lead to a higher share of skilled occupations in women’s employment. Bivariate analysis is used on the sample of 35,933 female labours out of 72,322 total labours in the dataset. The selected variables that affect the participation of women labour force are educational attainment, age of the female, state, stratum, ethnic group and marital status. Labour Force Survey 2015 is the main data source used in this study. The study found that the selected variables have a significant effect on female labour force status. In conclusion, cooperation from various authorities is essential to boost the participation of female in the labour market.